Personalized radiotherapy of brain metastases: survival prediction by means of dichotomized or differentiated blood test results? - Nieder, Carsten; Andratschke, Nicolaus H.; Grosu, Anca L. (Frontiers in Oncology, 2023)
Background and objectives: The validated LabBM score (laboratory parameters in patients with brain metastases) represents a widely applicable survival prediction model, which incorporates 5 blood test results (serum lactate dehydrogenase (LDH), C-reactive protein (CRP), albumin, platelets and hemoglobin). All tests are classified as normal or abnormal, without accounting for the wide range of abnormality observed in practice. We tested the hypothesis that improved stratification might be possible, if more granular test results are employed. Methods: Retrospective analysis of 198 patients managed with primary whole-brain radiotherapy in one of the institutions who validated the original LabBM score. Results: For two blood tests (albumin, CRP), discrimination was best for the original dichotomized version (normal/abnormal). For two others (LDH, hemoglobin), a three-tiered classification was best. The number of patients with low platelet count was not large enough for detailed analyses. A modified LabBM score was developed, which separates the intermediate of originally 3 prognostic groups into 2 statistically significantly different strata, resulting in a 4-tiered score. Conclusion: This initial proof-of-principle study suggests that granular blood test results might contribute to further improvement of the score, or alternatively development of a nomogram, if additional large-scale studies confirm the encouraging results of the present analysis.